Stability of arbitrarily switched discrete-time linear singular systems of index-1 - Pham, Thi Linh (H. : ĐHQGHN, 2019)
In this paper, the index-1 notion for arbitrarily switched discrete-time linear singular systems (SDLS) has been introduced. Based on the Bohl exponents of SDLS as well as properties of associated positive switched systems, some necessary and sufficient conditions have been established for exponential stability.